2019
DOI: 10.1371/journal.pone.0220735
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Auditory Stroop Task to increase cognitive load in walking tasks in healthy elderly and persons with Parkinson’s disease

Abstract: Background The development of treatments for freezing of gait (FOG) in Parkinson's disease (PD) requires experimental study setups in which FOG is likely to occur, and is amenable to therapeutic interventions. We explore whether the 'Auditory Stroop Task' (AST) can be used to increase cognitive load (and thereby elicit FOG), simultaneously with visual cues (as a therapeutic intervention for FOG). We additionally examined how these two contrasting effects might interact in affecting gait and FOG parameters. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Naismith et al (2010) highlighted a relation between FoG and TMT B. Previous studies showed a relation between cognitive functions and gait (Montero-Odasso et al, 2012), as well as between cognitive functions and FoG (Giladi and Hausdorff, 2006; Spildooren et al, 2010; Janssen et al, 2019): together with the understanding of the effects of the dopaminergic drugs, results from these studies could partially explain why patients with FoG can improve or, conversely, worse the quality of their gait depending on the cognitive load (Muralidharan et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
“…Naismith et al (2010) highlighted a relation between FoG and TMT B. Previous studies showed a relation between cognitive functions and gait (Montero-Odasso et al, 2012), as well as between cognitive functions and FoG (Giladi and Hausdorff, 2006; Spildooren et al, 2010; Janssen et al, 2019): together with the understanding of the effects of the dopaminergic drugs, results from these studies could partially explain why patients with FoG can improve or, conversely, worse the quality of their gait depending on the cognitive load (Muralidharan et al, 2017).…”
Section: Discussionmentioning
confidence: 80%
“…A cognitive task addressing executive functions such as set shifting and inhibition was then introduced. The auditory Stroop task was selected as it has been previously proven valid 33 and reliable (gait speed intraclass correlation coefficient [ICC] .91, and reaction time ICC .82) 34 during DT gait assessments in PD. The auditory Stroop task has been proven feasible to perform within the current context, 35 and also allows for the analysis of multiple performance outcomes (such as reaction times, intraindividual variability of reaction times, as well as accuracy).…”
Section: Methodsmentioning
confidence: 99%
“…The gait tasks were conducted under three different conditions in a pseudo-randomized order: with a cognitive dual-task (cDT), with a motor dual-task (mDT), and without a dual-task (noDT). The cDT consisted of the Adjusted Auditory Stroop Task, which is speci cally designed to increase cognitive workload in people with PD (19). In short, participants are asked to start or continue walking when hearing a congruent command (i.e., a male voice saying 'man' or a female voice saying 'woman'), and to stand still when hearing an incongruent command (i.e., a male voice saying 'woman' or a female voice saying 'man').…”
Section: Methodsmentioning
confidence: 99%